Water-swellable composition and water cut-off construction method
A composition with a matrix polymer, liquid rubber, solid elastomer, water-absorbing resin, and fibrous organic compound addresses shape retention and adherence issues, enabling effective water-stopping in complex applications.
Patent Information
- Application Number
- JP2023102035
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-21
- Publication Date
- 2025-01-09
- Estimated Expiration
- 2043-06-21
AI Technical Summary
Existing water-swellable compositions used in civil engineering face challenges with shape retention, deformability, and adherence issues, particularly when applied to complex shapes, leading to poor workability and ineffective water-stopping performance.
A composition comprising a matrix polymer with a specific formulation of liquid rubber, solid elastomer, water-absorbing resin, fibrous organic compound, and inorganic compound, which provides excellent water-swellability, shape retention, and non-adherence properties.
The composition can be easily molded to fit complex shapes, maintains its form after swelling, and prevents adherence to tools, ensuring effective water-stopping performance.
Smart Images

Figure 2025002107000001 
Figure 2025002107000002 
Figure 2025002107000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a water-expandable composition and a waterproofing method. [Background technology]
[0002] In the fields of civil engineering and construction, water-expanding water-stopping materials formed into tapes or films are used at the connections of various pipes, such as tunnel segments, underground Hume pipes, and U-shaped gutters for water supply and sewerage, to prevent water leakage and stop water leakage.
[0003] For example, Patent Document 1 discloses a water-expandable foam sealant obtained by adding a highly water-absorbent resin containing a crosslinked sodium polyacrylate, silica, a nonionic surfactant, a vulcanizing agent and a vulcanization accelerator, and a thermally decomposable foaming agent to a vulcanizable rubber, and subjecting the resulting mixture to a vulcanization and foaming treatment, with the aim of providing a water-expandable foam sealant that exhibits good expansion properties in water and ionized water such as seawater, has a small amount of elution into water, and is lightweight and easy to install.
[0004] Patent Document 2 discloses a water-stopping material for use around pipes, which comprises a water-stopping material main body molded from a composition containing a water-swellable clay and an organic adhesive, and a metal or resin core part wound into a coil shape and built into the water-stopping material main body, characterized in that a protective layer made of an alkali-decomposable resin film or a water-soluble resin film is provided on one outer surface of the water-stopping material main body, and a peel-off layer is provided on the other outer surface. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2007-063450 A [Patent Document 2] JP 2006-037642 A Summary of the Invention [Problem to be solved by the invention]
[0006] A sealant manufactured using a water-swellable composition absorbs water when it comes into contact with water and expands in volume, thereby exerting water-stopping properties. Such sealants are required to have water-swelling properties and shape retention properties that do not collapse even when they absorb water and expand. In addition, since the water-swellable compositions in Patent Documents 1 and 2 are in the form of a tape or sheet, if the shape of the area to be waterproofed is complex, it is difficult to freely deform the water-swellable composition to fit the shape and apply it. In addition, although it is possible to improve the deformability of the water-swellable composition by blending a liquid compound, there is a problem that the composition adheres to tools used for attaching the composition, such as gloves, resulting in poor workability.
[0007] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a water-swellable composition that is excellent in water-swellability, shape retention after water expansion, non-adhesiveness, and deformability. [Means for solving the problem]
[0008] The present inventors have conducted extensive research to solve the above problems, and as a result have found that the above problems can be solved by using a composition with a specific blend ratio, which has led to the completion of the present invention.
[0009] That is, the present invention is as follows. [1] A water-swellable composition comprising 5 to 100 parts by mass of a water-absorbent resin and 5 to 100 parts by mass of a fibrous organic compound per 100 parts by mass of a matrix polymer, the matrix polymer comprising a liquid rubber and a solid elastomer, and the liquid rubber amounting to 10 to 90% by mass of the total 100% by mass of the liquid rubber and the solid elastomer. [2] The water-swellable composition according to [1], further comprising 100 to 800 parts by mass of an inorganic compound. [3] The water-swellable composition according to [1] or [2], further comprising 50 to 300 parts by mass of a softener. [4] The water-swellable composition according to any one of [1] to [3], wherein the solid elastomer comprises a butyl-based rubber. [5] The water-swellable composition according to [2], wherein the inorganic compound contains 3 mass% or more of silica and / or clay minerals. [6] The water-swellable composition according to any one of [1] to [5], wherein the water-absorbent resin contains an alkylene oxide polymer. [7] The water-swellable composition according to any one of [1] to [6], wherein the average fiber length of the fibrous organic compound is 0.5 to 10 mm. [8] The water-swellable composition according to any one of [1] to [7], which is in a putty form. [9] The water-swellable composition according to any one of [1] to [8], which is used as a sealing material.
[10] A waterproof construction method comprising a step of applying the water-swellable composition according to any one of [1] to [9] to a location to be waterproofed. Effect of the Invention
[0010] According to the present invention, it is possible to provide a water-swellable composition that is excellent in water-swellability, shape retention after water expansion, non-adhesiveness, and deformability.
[0011] Since the water-expandable composition of the present invention has excellent deformability, it can be used as a putty-like composition and can be used according to the shape of the area to be waterproofed (for example, the connection parts of various pipes, etc.). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] [Water-expandable composition] The water-swellable composition of the present invention includes a matrix polymer, a water-absorbent resin, and a fibrous organic compound. The water-swellable composition includes 5 to 100 parts by mass of the water-absorbent resin and 5 to 100 parts by mass of the fibrous organic compound, relative to 100 parts by mass of the matrix polymer. Such a water-swellable composition is a composition with excellent deformability, and can be used as a putty that can be easily used according to the shape. That is, the composition can be provided as a putty-like water-swellable composition.
[0013] <Matrix polymer> Matrix polymers include liquid rubbers and solid elastomers.
[0014] In the present invention, the solid elastomer may be any elastomer that is solid at 25° C. Examples of solid elastomers include natural rubber, isoprene rubber, butadiene rubber, 1,2-polybutadiene rubber, styrene-butadiene rubber, chloroprene rubber, nitrile rubber, chlorinated polyethylene rubber, ethylene-propylene rubber, ethylene-propylene-diene rubber (EPDM), ethylene-vinyl acetate rubber, chloroprene rubber, chlorosulfonated polyethylene, acrylic rubber, epichlorohydrin rubber, crosslinkable rubber such as reclaimed rubber, silicone rubber, fluororubber, urethane rubber, butyl rubber, etc. One or more solid elastomers selected from these may be included.
[0015] In the present invention, butyl-based rubber means a rubber containing a butyl-based polymer containing a monomer unit derived from isobutylene. That is, the butyl-based rubber contains an isobutylene monomer unit. Moreover, the butyl-based rubber according to one embodiment of the present invention can contain an isobutylene monomer unit and an isoprene monomer unit, that is, it can contain a copolymer obtained by copolymerizing raw material monomers containing isobutylene and isoprene. Examples of butyl-based rubber include butyl rubber, partially crosslinked butyl rubber, reclaimed butyl rubber, polyisobutylene, chlorinated butyl rubber, and brominated butyl rubber. It can contain one or more butyl-based rubbers selected from these. The reclaimed rubber is a rubber obtained by subjecting vulcanized rubber to heat, pressure, and physical treatment to give it adhesion and plasticity again so that it can be used for the same purpose as the raw rubber. The partially crosslinked rubber is a rubber obtained by partially crosslinking uncrosslinked rubber with a crosslinking agent and a crosslinking assistant.
[0016] The solid elastomer preferably contains a butyl-based rubber. The inclusion of the butyl-based rubber provides the effect of providing good flexibility and water resistance. The proportion of the butyl-based rubber in the solid elastomer is, for example, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, or 100% by mass, and may be within a range between any two of the numerical values exemplified here.
[0017] In the present invention, the liquid rubber may be any rubber that has fluidity at 25° C. Examples of the liquid rubber include polyolefin-based thermoplastic elastomers, polyurethane-based thermoplastic elastomers, polyester-based thermoplastic elastomers, polyamide-based thermoplastic elastomers, polybutadiene-based thermoplastic elastomers, and styrene-based thermoplastic elastomers. One or more liquid rubbers selected from these may be included.
[0018] These rubbers and / or elastomers may be used alone or in combination of two or more.
[0019] The matrix polymer contains liquid rubber and solid elastomer, and contains 10 to 90% by mass of liquid rubber in 100% by mass of the total of liquid rubber and solid elastomer. The ratio of liquid rubber is preferably 25 to 75% by mass, more preferably 35 to 65% by mass. If the ratio of liquid rubber exceeds 90% by mass, non-adhesiveness is deteriorated, and if the ratio of liquid rubber is less than 10% by mass, deformability is deteriorated. Specifically, the ratio of liquid rubber is, for example, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90% by mass in 100% by mass of the total of liquid rubber and solid elastomer, and may be within the range between any two of the numerical values exemplified here.
[0020] <Water absorbent resin> The water-absorbing resin is also called SAP (Super Absorbent Polymer), and is a polymer having a water-absorbing ability to absorb, for example, 300 to 2000 times its own weight in water, and a water-retaining ability to hold the water in a very stable state. The water-absorbing resin is not particularly limited, but examples thereof include partially neutralized polyacrylic acid (e.g., partial sodium salt of acrylic acid polymer, partial sodium salt of acrylic acid graft polymer) and crosslinked bodies thereof, starch-acrylic acid graft polymer salt and crosslinked bodies thereof, saponified vinyl acetate-acrylic acid ester copolymer and crosslinked bodies thereof, 2-acrylamido-2-methylpropanesulfonic acid-acrylic acid copolymer salt and crosslinked bodies thereof, cellulose compounds such as sodium carboxymethylcellulose and ammonium carboxymethylcellulose, alkylene oxide polymers such as polyalkylene oxide and modified polyalkylene oxide, hydrolyzate of starch-acrylonitrile graft polymer, hydrolyzate of acrylonitrile copolymer or acrylamide copolymer or crosslinked bodies thereof, crosslinked bodies of cationic monomers, crosslinked isobutylene-maleic acid copolymer, etc. The water-absorbing resin may be used alone or in combination of two or more kinds, and may be in the form of powder or fiber.
[0021] Among these, alkylene oxide polymers are more preferable. By using such a water-absorbing resin, the shape stability after swelling with water tends to be further improved.
[0022] The content of the water-absorbent resin is 5 to 100 parts by mass, preferably 14 to 80 parts by mass, and more preferably 22 to 55 parts by mass, relative to 100 parts by mass of the matrix polymer. If the content of the water-absorbent resin is less than 5 parts by mass, the water-swelling property is poor. If the content of the water-absorbent resin is more than 100 parts by mass, the shape retention after water-swelling is poor. Specifically, the content of the water-absorbent resin is, for example, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, or 100 parts by mass relative to 100 parts by mass of the matrix polymer, and may be within a range between any two of the numerical values exemplified here.
[0023] <Fibrous organic compounds> The shape of the fibrous organic compound may be fibrous, and examples of the cross-sectional shape of the fiber include a circle, an ellipse, and a polygon. When the average fiber length of the fibrous organic compound is L and the average diameter is D, the L / D of the fiber is, for example, more than 10, preferably 50 or more, and more preferably 100 or more. The upper limit is not particularly specified, but is, for example, 10,000. The average diameter of the fibrous organic compound is, for example, 1 to 100 μm, preferably 2 to 50 μm, and more preferably 5 to 20 μm. The average fiber length of the fibrous organic compound is, for example, 0.1 to 15 mm, and preferably 1 to 10 mm. The average fiber length of the fibrous organic compound is specifically, for example, 0.1, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, or 15.0 mm, and may be within a range between any two of the numerical values exemplified here.
[0024] Examples of the fibrous organic compound include meta-aramid fibers, para-aramid fibers, amide fibers, pulp fibers, cellulose fibers (pulp fibers), polyparaphenylene benzobisoxazole fibers, polyarylate fibers, etc. It is preferable that the fibrous organic compound is contained in a state in which the fibers are dispersed in the composition.
[0025] The average fiber length and average diameter of a fibrous organic compound are determined by measuring the lengths of a sufficiently large number of fibrous organic compounds, i.e., 20 or more, and averaging the lengths.
[0026] The fiber length and diameter of the fibrous organic compound can be measured, for example, by using a field emission scanning electron microscope (FE-SEM).
[0027] The content of the fibrous organic compound is 5 to 100 parts by mass, preferably 10 to 80 parts by mass, and more preferably 20 to 55 parts by mass, relative to 100 parts by mass of the matrix polymer. If the content of the fibrous organic compound is less than 5 parts by mass, the shape retention after water expansion is poor and the material collapses during water expansion. On the other hand, if the content of the fibrous organic compound is more than 100 parts by mass, the deformability is poor. Specifically, the content of the fibrous organic compound is, for example, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, or 100 parts by mass relative to 100 parts by mass of the matrix polymer, and may be within a range between any two of the numerical values exemplified here.
[0028] <Inorganic compounds> The water-expandable composition of the present invention may contain an inorganic compound. Examples of the inorganic compound include metal oxides such as alumina, aluminosilicate, zinc oxide, titanium oxide, calcium oxide, magnesium oxide, iron oxide, tin oxide, antimony oxide, aluminum hydroxide, and ferrites; hydrated inorganic substances such as calcium hydroxide, magnesium hydroxide, aluminum hydroxide, and hydrotalcite; metal carbonates such as basic magnesium carbonate, calcium carbonate, magnesium carbonate, zinc carbonate, strontium carbonate, and barium carbonate; calcium salts such as calcium sulfate and calcium silicate; glass. Examples include beads, silica-based balloons, aluminum nitride, boron nitride, silicon nitride, carbon black, graphite, carbon balloons, charcoal powder, various metal powders, potassium titanate, magnesium sulfate, lead zirconate titanate, aluminum borate, molybdenum sulfide, silicon carbide, zinc borate, various magnetic powders, fly ash, inorganic hollow fillers, perlite, obsidian, perlite, rosin, diatomaceous earth, dewatered sludge, boron, sodium tetraborate hydrate (borax), inorganic phosphorus compounds, glass fibers, silica, and clay minerals.
[0029] Among these, it is preferable that silica and / or clay minerals are included. As the clay mineral, at least one selected from natural or synthetic inorganic clay minerals is used. As the clay mineral, smectite clays such as bentonite, montmorillonite, and hectorite, fibrous clays such as sepiolite and palygorskite, sericite, illite, glauconite, chlorite, talc, zeolite, beidellite, nontronite, saponite, hectorite, sauconite, stevensite, cristopalite, smectite, kaolin, clay (hydrated aluminum silicate), and the like can be mentioned. These inorganic compounds may be used alone or in combination of two or more.
[0030] The content of the inorganic compound is preferably 100 to 800 parts by mass, more preferably 200 to 700 parts by mass, and even more preferably 300 to 550 parts by mass, relative to 100 parts by mass of the matrix polymer, which is an elastomer, a rubber, or a combination thereof. By having the content of the inorganic compound of 100 to 800 parts by mass, good non-adhesiveness and deformability can be obtained. Specifically, the content of the inorganic compound is, for example, 100, 150, 200, 250, 300, 350, 400, 450, 500, 550, 600, 650, 700, 750, or 800 parts by mass relative to 100 parts by mass of the matrix polymer, and may be within a range between any two of the numerical values exemplified here.
[0031] The content of silica and / or clay mineral in the inorganic compound is preferably 3 mass% or more, and good water expansion properties can be obtained within such a range. The content of silica and / or clay mineral in the inorganic compound is specifically, for example, 0, 1, 3, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, and may be within a range between any two of the numerical values exemplified here.
[0032] <Softener> The water-swellable composition of the present invention may contain a softener. The softener is used to impart flexibility to the water-swellable composition, and is preferably one that is fluid at room temperature. The softener is not particularly limited, and one or more known softeners may be freely selected and used. Examples of the softener include paraffinic or naphthenic process oils, mineral oils, vegetable oils, paraffins such as liquid paraffin, waxes, phthalic acid, adipic acid, sebacic acid or phosphoric acid ester plasticizers, stearic acid or its esters, etc.
[0033] The content of the softener is preferably 50 to 300 parts by mass, more preferably 50 to 250 parts by mass, and further preferably 50 to 190 parts by mass, relative to 100 parts by mass of the matrix polymer. When the content of the softener is 50 to 300 parts by mass, good deformability and non-adhesiveness can be obtained. Specifically, the content of the softener is, for example, 0, 25, 48, 50, 75, 100, 125, 150, 175, 200, 225, 250, 275, or 300 parts by mass relative to 100 parts by mass of the matrix polymer, and may be within a range between any two of the numerical values exemplified here.
[0034] <Other additives> In addition to the above-mentioned components, the water-swellable composition of the present invention may contain additives such as crosslinking agents, crosslinking assistants, antioxidants, ultraviolet protection agents, lubricants, dispersants, and tackifiers which are commonly used in rubbers, if necessary. When a crosslinking agent or crosslinking assistant is used, the total amount is preferably 0.05 parts by mass or less, or 0.01 parts by mass or less.
[0035] <Aspects> The water-expandable composition of the present invention is preferably used as a sealant. The sealant produced using the water-expandable composition of the present embodiment can be suitably used for applications as a water-stopping member in civil engineering such as shield construction segments, box culverts, flumes (steel frames, benches), Hume pipes, manhole joints, reservoirs, water channels, pools, etc., and concrete joints; as a water-stopping member in architecture such as various water tanks, H-steel surroundings, and various joints; as a water-stopping member in housing equipment such as water purification tanks, water receiving tanks, and unit baths. In addition, the sealant produced using the water-expandable composition of the present embodiment can exert a sufficient water-stopping effect even when used in the connection parts of concrete products used in water channels for not only fresh water but also seawater.
[0036] <Production method and uses of water-expandable composition> The water-swellable composition of the present invention can be produced by kneading the necessary components.
[0037] The device for kneading the compound includes a conventional kneading device such as a mixer, a Banbury mixer, a kneader mixer, or a two-roll mill.
[0038] [Water stop construction method] The above-mentioned water-swellable composition can be used by attaching (supplying) it to the connection of various pipes or other water-stopping target locations that require water-stopping treatment. The water-stopping construction method according to one embodiment of the present invention includes a step (application step) of applying the above-mentioned water-swellable composition to the water-stopping target locations. The water-stopping construction method may also include an application step of applying the water-swellable composition to the water-stopping target locations of one or both of two members to be connected, and a step (connection step) of connecting the two members after the application step.
[0039] The method for applying the water-expandable composition to the area to be waterproofed is not particularly limited, but it can be done, for example, by hand (e.g., bare hand or gloved hand), application with a trowel, spatula, or brush, extrusion from a container such as a tube, or a combination of these. EXAMPLES
[0040] The present invention will now be described in more detail with reference to the following examples, in which the unit of the amount of each substance used is parts by mass.
[0041] 1. Preparation of Water-Swellable Composition The components shown in Table 1 were kneaded for 10 minutes at 100° C. using a 3 L pressure kneader (manufactured by Moriyama Co., Ltd., model: DS3-10MWB-S) to obtain water-swellable compositions of Examples and Comparative Examples. The amount of each substance used in Tables 1 to 6 is in parts by mass unless otherwise specified.
[0042] [Table 1]
[0043] [Table 2]
[0044] [Table 3]
[0045] [Table 4]
[0046] [Table 5]
[0047] [Table 6]
[0048] Details of each component in Tables 1 to 6 are as follows. <Matrix polymer> [Liquid rubber] Polyisoprene rubber: Kuraray Co., Ltd. "LIR-30", molecular weight 28000, Tg-63℃, viscosity 70Pa.s (38℃) Polybutadiene rubber: Kuraray Co., Ltd. "LBR-302", molecular weight 5500, Tg-85℃, viscosity 0.6Pa.s (38℃) Polybutene: JX Nippon Oil & Energy Corporation, "HV-100", molecular weight 980, kinematic viscosity 9,500 mm2 / s (40℃) [Solid elastomer] Butyl rubber: JSR Corporation "Butyl 268", rubber-like (40℃) Partially cross-linked butyl rubber: Royal Elastomers, "KALAR5280" <Water absorbent resin> - Acrylic acid polymer sodium (Na) salt crosslinker: "AQUALIC CS-6S" manufactured by Nippon Shokubai Co., Ltd. Modified polyalkylene oxide: "Aquacoke TWB" manufactured by Sumitomo Seika Chemicals Co., Ltd. <Inorganic compounds> Silica: Tosoh Silica Corporation, "Nipsil VN3" Sepiolite (clay mineral): "Miraclair P150" manufactured by Omi Mining Co., Ltd. Bentonite (clay mineral): "Akagi" manufactured by Hojun Co., Ltd. Calcium carbonate (Ca): "TA-044" manufactured by Chichibu Lime Industry Co., Ltd. <Softener> Process oil: Idemitsu Kosan Co., Ltd., "Diana Process Oil NP-24", kinematic viscosity 23.25 mm 2 / s(40℃) <Fibrous organic compounds> Pulp fiber, average fiber length 1.2 mm: "Neofiber NS-10" manufactured by Oji Seibaku Co., Ltd. Aramid fiber, 0.25, 0.5, 3, 10, 12 mm: Twaron Short Cut Fiber manufactured by Teijin Limited
[0049] 2. Evaluation The water-swellable compositions obtained in the Examples and Comparative Examples were subjected to various evaluations as shown below.
[0050] <Deformability (softness)> The water-swellable composition was processed into a sheet-like molded body having a thickness of 2 mm using a press (temperature: 80°C, time: 1 minute), and the obtained molded body (specimen 1) was used to measure the softness of the specimen 1 at a load of 150 g and a temperature of 21°C in accordance with JIS A5752. A prescribed cone was penetrated vertically into the specimen 1, and the penetration depth was measured to the nearest 0.1 mm. Based on the penetration depth, the deformability was evaluated according to the following criteria. ◎: 60 [1 / 10 mm] or more ○: 50 [1 / 10 mm] or more and less than 60 [1 / 10 mm] △: 40[1 / 10mm] or more and less than 50[1 / 10mm] ×: Less than 40 [1 / 10 mm]
[0051] <Non-adhesive> A latex glove was put on, and 100 g of water-swellable composition was gripped 10 times. The mass of the substance attached to the glove was measured, and the amount of the substance attached was calculated based on the following formula. Based on the amount of the substance attached, the non-adhesiveness was evaluated according to the following criteria. The lower the non-adhesiveness, the easier the processing. Amount of attached substance (g) = (mass of glove after squeezing 100 g of water-swellable composition 10 times) - (original mass of glove) ◎: Less than 0.02[g] ○: 0.02[g] or more and less than 0.05[g] △: 0.05g or more and less than 0.10g ×: 0.10[g] or more
[0052] <Water swelling> According to JIS K-6258, 10 g of the water-swellable composition was molded into a spherical molded body (specimen 2), which was immersed in water at 23°C for 7 days, and the volume change rate before and after immersion was calculated using the following formula. The volume change rate before and after immersion is considered to indicate the amount of water supplied to specimen 2, i.e., the amount of volume change, and the water-swellability was evaluated according to the following evaluation criteria. Note that Comparative Examples 4 and 5 were marked as x because specimen 2 collapsed. Volume change rate (%) = ((cd)-(ab)) / (ab) x 100 a: Mass in air before immersion in water, b: Mass in water before immersion c: Mass in air after immersion in water, d: Mass in water after immersion (Evaluation Criteria) ◎: Volume change rate is 100% or more ○: Volume change rate is 80% or more but less than 100% △: Volume change rate is 60% or more but less than 80% ×: Volume change rate is less than 60%
[0053] <Shape retention after expansion with water> 5 g of the water-swellable composition was molded into a spherical molded body (test body 3) and immersed in water at 23° C. for 7 days. The shape retention of test body 3 was then visually observed and evaluated according to the following criteria. (Evaluation Criteria) ◎: No cracks were observed in specimen 3 after expansion with water. ○: Cracks were observed in test piece 3 after it expanded with water, but it did not crumble when it was taken out of the water. ×: When the test piece 3 after swelling in water was taken out of the water, it collapsed.
Claims
1. The composition contains 5 to 100 parts by mass of a water-absorbent resin and 5 to 100 parts by mass of a fibrous organic compound relative to 100 parts by mass of a matrix polymer, The water-swellable composition, wherein the matrix polymer contains a liquid rubber and a solid elastomer, and the liquid rubber is contained in an amount of 10 to 90% by mass with the total amount of the liquid rubber and the solid elastomer being 100% by mass.
2. 10. The water-swellable composition of claim 1 further comprising 100 to 800 parts by weight of an inorganic compound.
3. 10. The water-swellable composition of claim 1 further comprising 50 to 300 parts by weight of a softener.
4. 2. The water-swellable composition of claim 1, wherein the solid elastomer comprises a butyl-based rubber.
5. 3. The water-swellable composition according to claim 2, wherein the inorganic compound contains 3% by weight or more of silica and / or clay minerals.
6. 2. The water-swellable composition of claim 1, wherein the water-absorbent resin comprises an alkylene oxide polymer.
7. 2. The water-swellable composition according to claim 1, wherein the average fiber length of the fibrous organic compound is 0.5 to 10 mm.
8. The water-swellable composition according to any one of claims 1 to 7, which is in the form of a putty.
9. The water-expandable composition according to any one of claims 1 to 7, which is used as a sealing material.
10. A water-stop construction method comprising the step of applying the water-expandable composition according to any one of claims 1 to 7 to a location to be water-stopped.
Citation Information
Patent Citations
Composition for water-swelling waterstop material
JP1992178485A
Water-absorbent resin composition
JP1994157839A
Water-expansible water cut-off material and working method therefor
JP2002180031A
Rubber composition for flexible coupling and flexible coupling using the same
JP2003028361A
Water-swelling waterproofing composition
JP2023059628A